Urubamba: The biodiversity of a Peruvian rainforest - Alonso, Alfonso; Dallmeier, Francisco; Campbell, Patrick (Estados Unidos: Smithsonian Institution, 2001)
The lower Urubamba region, Peru; The vegetation communities of the lower Urubamba region, Peru; Orchids of the lower Urubamba region, Peru; Biodiversity assessment of the aquatic systems of the lower Urubamba region, Peru; Diversity of land mollusks in the Bamboo-dominated forest of the lower Urubamba region, Peru; Biodiversity assessment of the Arthropods of the lower Urubamba region, Peru; Diversity and community structure of the spiders of the lower Urubamba region, Peru; Assessment of the scorpions of the lower Urubamba region, Peru; Species richness of the wasp community of the lower Urubamba region, Peru; Assessment of the ants of the lower Urubamba region, Peru; Biodiversity assessment of the diurnal butterflies of the lower Urubamba region, Peru; Biodiversity assesssment of the nocturnal butterflies of the lower Urubamba region, Peru; Biodiversity assessment of the hedylidae of the lower Urubamba region, Peru; Diversity and trophic relationships of dung Beetles of the lower Urubamba region, Peru; Assessment of amphibians and reptiles of the lower Urubamba region, Peru; Diversity and conservation of fish of the lower Urubamba region, Peru; Structure and composition of the birds communities of the lower Urubamba region, Peru; The small mammal community of the lower Urubamba region, Peru; Assessment of the large mammals of the lower Urubamba region, Peru; Ectoparasites of small mammals of the lower Urubamba region, Peru
Ingles